PENDAMPINGAN PENENTUAN PRIORITAS PELATIHAN BAGI PETERNAK BABI DI DESA WAE LOLOS KABUPATEN MANGGARAI BARAT - Wigbertus Gaut Utama; Roselin Gultom; Hendrikus Demon Tukan; Puspita Cahya Achmadi (Unika Santu Paulus Ruteng, 2023)
One form of empowering farmers is providing continuous and contextual training. In its implementation, the training must be truly based on the needs of the farmers themselves. This is in line with the